Ku nowej koncepcji natchnienia LXX - Mielcarek, Krzysztof (The Biblical Annals, 2017)
The article gives a short panorama of questions concerning the inspiration of Septuagint. A little sketch of catholic teaching on the inspiratlffin of the Scripture is a starting point of this paper. It is followed by two historical paragraphs devoted to both Jewish-Hellenistic and early Christian witnesses, who seem to support the idea of divine inspiration of the Greek text. Finally, some general issues debated by contemporary scholars are presented. In conclusion, not rejecting the TM as the basis for modern OT translątions, the author favours the idea of LXX’s inspiration. However, since the research on the LXX is still in its early stadium, one has to be careful not to give too precipitate answer in such a complicated matter.